Stem-Based Teaching Material Needs Analysis to Improve Student Creativity - Nuryanti, Dwi; Nuryadi, N (Universitas Muhammadiyah Surakarta, 2022)
Innovation is the most important key in the 4.0 industrial era which requires education units to form students who have 21st century competencies and able to think critically, creatively, collaboratively, and communicatively. The STEM approach is one of the learning innovations that developed in the revolution 4.0 industrial era. STEM stands for Science, Technology, Engineering, and Mathematics. Learning with the STEM approach is identified as learning that combines four disciplines, namely Science, Technology, Engineering and Mathematics with a focus on the learning process that explores two or more fields that involve students actively in the context of problem solving in the real world. The Integrated application of STEM requires teachers and students to think creatively. The purpose of this study is to describe the need for STEM-based mathematics teaching materials that can increase students' creativity. This type of research is descriptive qualitative. The research subjects were students of 8^th grade of SMP Negeri 3 Tempel (State Junior High School). Data collection techniques used interviews, observations, and tests. Data analysis used the Miles and Huberman model which consisted of data reduction, displaying data, and drawing Conclusion or verification. This research has several results. First, students' creative abilities are still relatively low. Second, the learning model and teaching materials used are less stimulating for students to improve their creativity abilities. Third, STEM-based learning can help students to improve students' creativity. From the results, this study concludes that STEM-based mathematics teaching materials that could stimulate students' creativity abilities need to be developed.